Comparison of Multilevel Inverters for the Reduction of Common Mode Voltage - Muhammad Jamil (Institute of Advanced Engineering and Science, 2013)
This paper presents a comparison between NPC (neutral point clamped) and H-cascaded multilevel inverters by considering the increas or decrease of harmonics in the output line to line voltages, phase voltages and common mode voltage. Multilevel voltage source converters are getting increased importance for applications in the medium and high voltage range. A conventional two-level PWM (pulse width modulated) inverter generates high frequency common mode voltage with high dv/dt. In the same way, commonly used multilevel inverter modulation schemes generate common mode voltage. Common mode voltage may cause motor shaft voltages, bearing currents and EMI (electromagnetic interference). Common mode voltage depends not only on switching method but also on earth mass. The use of earth mass on a proper pl.DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.3605